Efeito de extratos de microalgas na germinação e crescimento inicial de plantas de milho - Weissheimer, Leandro (2024)
Population growth and the demands of the processing industry have created significant challenges for grain supply, particularly with respect to increasing corn productivity. To meet the growing demand for food, there is a continuous search for innovative and effective approaches. In this context, algae-derived bioinputs have garnered great interest in agriculture due to their biodegradable nature, ability to restore soil fertility, and potential for bio-stimulating plant growth. This study aimed to evaluate the effects of microalgae extracts cultivated in photobioreactors on the germination and initial growth of corn plants. The research included an analysis of the mineral composition of biomass from different strains of microalgae cultivated in photobioreactors with CO₂ supplementation. Extracts with different biomass concentrations (0 [control], 250, 500, 750, and 1000 mg) from the strains PPEQ-01, PPEQ-02, PPEQ-04, PPEQ-05, PPEQ- 07, and PPEQ-08, combined with different extracting substances (DMSO and H₂O), were prepared and evaluated using a factorial experiment to analyze germination percentage as well as fresh and dry weights of the seedlings after seed incubation in a BOD chamber at 25°C for 7 days. Additionally, the effect of seed inoculation with extracts containing 500 mg biomass of the aforementioned strains, and the control, in combination with DMSO and H₂O extractors, was assessed on plant height, fresh and dry weights of the shoot and root system, along with root parameters evaluated by the WinRhizo system. The results showed a wide variation in the mineral composition of the microalgae, highlighting strains PPEQ-01 and PPEQ-07 as the most promising due to their higher nutrient content. Seed viability tests showed that extracts from strains PPEQ-01, PPEQ- 02, PPEQ-04, PPEQ-05, and PPEQ-07 promoted an increase in germination percentage compared to the control. An increase in seedling dry weight was achieved with the use of strains PPEQ-01, PPEQ-05, and PPEQ-07. In greenhouse conditions, plant height, as well as shoot and root fresh and dry weights, were influenced by both the biomass type and the extractor used. Root length was affected by biomass type, regardless of the extractor. Strain PPEQ-01 showed the highest potential under the evaluated conditions. It is concluded that the optimal biomass amount and extractor type are critical to identifying extracts that promote the growth stimulation of corn plants.